Predicting uncertain behaviour of pulping system in a paper industry. (13th September 2010) - Sharma, S.P.; Kumar, Dinesh; Kumar, Ajay
To achieve the goal of high production and hence more profit in an organisation, each system/subsystem must remain operative for long duration. The industrial systems are complex in nature, configuration and capital oriented and so it is very difficult to analyse their failure pattern. The available information about these equipments is imprecise, incomplete, vague and conflicting. Therefore, management decisions are based on experience. The objective of this paper is to quantify the uncertainties which make the decision more realistic and generic for the considered industrial system. The study is conducted in a medium sized paper industry, comprised of subsystems namely – chipping, feeding, pulping, washing, screening, bleaching, paper production system, etc., arranged in a series configuration. Pulping system, the main functionary part of the paper industry, is the subject of present discussion. An interaction among the operative equipments has been developed using Petri net model and the steady state behaviour of the equipment has been analysed. The results will be helpful for reallocating the resources and for achieving the targeted goal of higher profit.